Susceptibility of Two Varieties Rice (Oryza sativa L.) on Saline Environment - Hariadi, Yuda C; Nurhayati, Arry Y; Endraningrum, A. (UNEJ e-Proceeding, 2014)
Serealia such as rice, wheat, and maize are very important world food demands, and rice was highest on the nutrional protein status with respect to amino acid composition. Rice (Oryza sativa) has been an important primary cereal for generations that supply around 90% of carbohydrate needs in Indonesia, that every effort to be made in acquiring the fullfillment demand. The research was aimed to investigate the tolerance of two rice varieties Towuti and Ciherang grown on fertile and arid soil on different salinity. Healthy and homogenous three weeks old seedlings were grown in a glasshouse on 0, 50mM, 100mM, 200mM, and 300mM of NaCl on plastic pots with two different soil, under a randomized design and five replicated five times. The growth in terms of leaf area and surface electrical potential difference were observed on a weekly basis for four weeks after the plants had been exposed. The result showed that leaf area and the electrical PD of both rice varieties were significantly reduced under fertile and arid soil under 200mM of NaCl and 300mmM of salinity. It is implied that the photosynthetic process was significantly affected by salinity and was concluded that both varieties were sensitive to salinity at 200mM of NaCl. There was possibility that the protein content was involved on the osmotic change on the salinity process, element supplements were needed, but there is a need for less expensive methods. Keywords: salinity, rice; protein, electrical PD, growth